2017
DOI: 10.3201/eid2307.161858
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Infection with Hepatitis C Virus andStreptococcus pneumoniae

Abstract: Little is known about concurrent infection with hepatitis C virus (HCV) and Streptococcus pneumoniae, which causes invasive pneumococcal disease (IPD). We hypothesized that co-infection with HCV and S. pneumoniae would increase risk for death and complications. We captured sociodemographic and serologic data for adults with IPD in a population-based cohort study in northern Alberta, Canada, during 2000–2014. IPD patients infected with HCV were compared with IPD patients not infected with HCV for risk of in-hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
1
15
0
2
Order By: Relevance
“…As these patients got older, liver disease progressed, and the burden of chronic hepatitis C disease increased [ 38 ]. Additionally, cirrhosis increases the risk of infections due to unspecific immune dysfunctions added to the increased bacterial translocation [ 12 , 13 , 17 ], and the predisposition of patients infected with HCV to develop other infectious diseases [ 9 , 10 , 11 ]. Once the infection is established, the excessive immune response plus the hemodynamic dysfunction related to cirrhosis favors the development of sepsis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As these patients got older, liver disease progressed, and the burden of chronic hepatitis C disease increased [ 38 ]. Additionally, cirrhosis increases the risk of infections due to unspecific immune dysfunctions added to the increased bacterial translocation [ 12 , 13 , 17 ], and the predisposition of patients infected with HCV to develop other infectious diseases [ 9 , 10 , 11 ]. Once the infection is established, the excessive immune response plus the hemodynamic dysfunction related to cirrhosis favors the development of sepsis [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown an increased risk of bacterial infection and sepsis in HCV-infected patients [ 14 , 15 , 62 ], even if they have not developed cirrhosis [ 10 , 16 ]. In HCV-infected patients, invasive pneumococcal disease [ 9 ] and Staphylococcus aureus infection [ 63 ] are among the most common bacterial infections. In cirrhotic patients, the endogen infections due to enteric Gram (−) bacteria and Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dessa forma, esses dados demonstram a importância de se buscar a presença de distúrbios psiquiátricos entre indivíduos infectados pelo vírus da hepatite C, para que assim possam ser trabalhadas medidas de prevenção para eventos que podem, como visto, levarem a um incremento da morbimortalidade.No presente estudo, as infecções estiveram associadas a um risco quase três vezes maior de morte em indivíduos positivos para o HCV. Uma associação entre a infecção pelo HCV e risco aumentado para infecções bacterianas já foi relatada anteriormente[122][123][124][125][126] . Tuberculose, pneumonia adquirida na comunidade ou infecções bacterianas entre pacientes em hemodiálise são muito mais frequentes em indivíduos infectados pelo HCV[122][123][124][125][126] .…”
unclassified
“…Uma associação entre a infecção pelo HCV e risco aumentado para infecções bacterianas já foi relatada anteriormente[122][123][124][125][126] . Tuberculose, pneumonia adquirida na comunidade ou infecções bacterianas entre pacientes em hemodiálise são muito mais frequentes em indivíduos infectados pelo HCV[122][123][124][125][126] . A coinfecção com o HIV e o uso de drogas injetáveis também são mais comuns em pacientes infectados pelo HCV e podem levar a maiores taxas de mortalidade por sepse15 .…”
unclassified